BayLum - an R package for Bayesian analysis of OSL ages: an introduction - Philippe, Anne; Guérin, Guillaume; Kreutzer, Sebastian (Quaternary geochronology, 2019)
We introduce a new R package ‘BayLum’ devoted to the analysis of OSL data and to construct chronological models in a Bayesian framework. Our contribution presents a summary of the statistical models, and introduces the main functions implemented in the package.
Online veröffentlicht: 18. Mai 2018, Artikelversion: 28 November 2018
Gesehen am 26.03.2025